Revealing research trends: a bibliometric review of publications on transformational leadership - Yulianto, Eko; Iskandar, Yusuf (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
This bibliometric review examines the landscape of research on transformational leadership, aiming to reveal current trends, influential authors, research themes, and future research directions. Through systematic data collection from reputable academic databases and analysis using VOS Viewer software, the study identifies a significant interest in transformational leadership, as evidenced by 200 papers and 211 citations within the past year. Key findings include the high impact of certain works, notable authors such as P. Charoensukmongkol and A.Ç. Kılınç, and central themes such as motivation and emotional intelligence. The study's implications extend to research advancement, educational practice, organizational leadership, policy-making, and global impact, highlighting the relevance and importance of transformational leadership in various contexts. This review enriches our understanding of transformational leadership and provides valuable insights for future research and practice. Although there has been much research on Transformational Leadership, there is still a need for more in-depth analysis to reveal emerging research trends, dominant research focuses, as well as research contributions to the understanding of this concept. In this regard, bibliometric research offers a powerful approach to analyze and present information about the distribution, trends and dynamics of research in the field of transformational leadership.The importance of understanding and uncovering research trends related to Transformational Leadership is not only driven by academic needs, but also by its practical implications in the context of organizations and leadership development. For example, findings from bibliometric analysis can provide guidance for organizations in developing leadership development programs that align with current trends and practices